2006
DOI: 10.1097/00001888-200601000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Sleep Quantity, Sleep Deprivation, Mood Disturbances, Empathy, and Burnout among Interns

Abstract: Given the association between chronic sleep deprivation and mood disturbances during internship, outcome assessment is warranted to see if duty-hour reform will translate into more hours slept or fewer hours worked, coincident with improved mood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
272
1
15

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 415 publications
(308 citation statements)
references
References 18 publications
20
272
1
15
Order By: Relevance
“…It is important to note that sleepiness and well‐being levels in senior residents did not return to baseline (PGY1 levels). Similar to our findings, a study evaluating PGY1 medical residents reported a significant increase in chronic sleep deprivation, depression, and burnout across the intern year 15. The same study noted a strong correlation between chronic sleep deprivation and the development of moderate depression 15.…”
Section: Discussionsupporting
confidence: 89%
“…It is important to note that sleepiness and well‐being levels in senior residents did not return to baseline (PGY1 levels). Similar to our findings, a study evaluating PGY1 medical residents reported a significant increase in chronic sleep deprivation, depression, and burnout across the intern year 15. The same study noted a strong correlation between chronic sleep deprivation and the development of moderate depression 15.…”
Section: Discussionsupporting
confidence: 89%
“…[35][36][37] Furthermore, reduction in empathy and increased risk for depression and burnout associated with chronic sleep deprivation in medical residents may jeopardize the quality of care delivered as well as the health of the care provider. 38 Similar concerns related to patient safety arise for nurses working night shifts. Nurses working nights are less alert and more likely to struggle to stay awake during the latter half of the shift than are nurses working permanent day or evening shifts.…”
Section: Patient Safetymentioning
confidence: 92%
“…Increasing autonomy and support 27 and decreasing workload might also decrease stress levels. 20,28,29 Our finding linking poor quality teamwork to stress and, in turn, to fatigue may provide further evidence of poor teamwork's contribution to errors. 30 Curricula teaching formal teamwork structure and process, 31 high fidelity simulation-based team training, 32 and training incorporating didactic instruction with interactive participation 33 have been shown to improve communication and enhance safety.…”
Section: Discussionmentioning
confidence: 57%